The Effect of Specifications Grading on Students’ Learning and Attitudes in an Undergraduate-Level Cell Biology Course - Shoshana D. Katzman; Jennifer Hurst-Kennedy; Alessandra Barrera; Jennell Talley; Elisabeth Javazon; Mary Diaz; Mary E. Anzovino (Journal of Microbiology & Biology Education, 2021)
ABSTRACT Specifications (specs) grading is a grading system in which mastery of specific educational outcomes is the basis for the final grade a student earns in the course. Implementation of the types of assessments used for specs grading has shown to be beneficial for student learning and motivation compared to traditional grading systems. We designed a specs grading strategy in an undergraduate Cell Biology course, creating 20 individual learning outcomes (LOs). The grade earned in lecture depended on the number of LOs the student mastered. If students were unable to master the content on their initial attempt, they could earn retakes for each LO assessment by completing an assignment associated with the information covered in that LO. A student’s final class grade was dependent on the number of LOs mastered combined with the grade earned on their final exam. Here, we present how specifications grading was implemented in Cell Biology, differences in overall grade distribution between grading systems, improved performance on content-related assessment questions in sections using specifications grading, and more-positive attitudes for sections using specifications grading than for traditionally graded sections.